Developing Writers of Argument: Tools and Rules That Sharpen Student Reasoning - Smith, Michael W; Imbrenda, Jon-Philip (Corwin Literacy, 2018)
The ability to make effective arguments is not only necessary in students’ academic lives, it’s a transferable skill that’s essential to students’ future success as critical thinkers and contributing members of society. But in the here and now, how do we engage students and ensure they understand argument writing’s fundamental components? How do we take them from “Here’s what I think” to “Here’s what I think. Here’s what makes me think that. And here’s why it matters”? This stunning, full-color book shows the way, with ready-to-implement lessons that make argument writing topical and relevant. Students are first asked to form arguments about subjects that matter to them, and then to reflect on the structure of those arguments, a process that provides learners with valuable, reusable structural models. • Throughout the book, the authors provide helpful instructional tools, including • Literary, nonfiction, and author-created simulated texts that inspire different points of view • Essential questions to create a context that rewards argumentation • Lessons introducing students to the three essential elements of an argument–claim, data, and warrant–and how to make each effective • Questioning probes, semantic differential scales, and other innovative instructional approaches • Samples of writing from the authors’ own students, and enlightening details on how this work informed the authors’ subsequent teaching approach Complete with guidance on applying the lessons’ techniques in a broader, unit-wide context, Developing Writers of Argument offers a practical approach for instructing students in this crucial aspect of their lifelong development.